Analysis of the Effect of Infrastructure System at Kendari New Port Terminal on Container Customer Satisfaction Using Principal Component Analysis (PCA) Method - Muhammad, Fadel; Natalia, Tia; Achmadi, Tri (International Journal of Offshore and Coastal Engineering (IJOCE), 2024)
Container Terminal Kendari New Port, located in Kendari, Southeast Sulawesi Province, is known to be one of the gateways for international logistics flow with adequate facilities and systems implemented where one of its activities is loading and unloading of containers supported by a reasonably large pier measuring 300 square meters. Even though it is equipped and supported by adequate infrastructure, it is not uncommon for customers to feel that the system and infrastructure provided are unsatisfactory. For this reason, in this study, satisfaction indicators are in the form of price (X1) and facilities (X2), and all of these variables have several indicators to determine customer satisfaction with the infrastructure offered using the PCA method. The PCA method is advantageous when the existing data has a large number of variables and has a correlation between the variables. In general, the principal component can be helpful for feature selection and interpretation of variables. The results of this study indicate that there is one variable that has an eigenvalue more significant than one, which indicates that this variable has a cumulative proportion of 58.278%, which means that 1 factor can absorb information in the data of 58.278% where the variable is Price (X1).